HUBUNGAN LAMA MENGIKUTI BABY SPA DENGAN KENAIKAN BERAT BADAN BAYI USIA 0-6 BULAN DI YAYASAN IBU SEJATI MANDIRI KECAMATAN TUNTUNGAN KOMPLEKS MEDAN PERMAI KOTA MEDAN TAHUN 2018 - Faradita Wahyuni; Rudi Purwana; Desyi Gusharni Matondang (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2020)
Abstract Background;Babies who attend baby spas on a regular basis will produce weight gain of up to 47% -80% for a month, while babies who do not regularly attend baby spas only 2 times a week experience a weight gain of 15-30%. Objectives;The purpose of this study is to find out the Relationship of the Length in Attending Baby Spa with 0-6 Months Old Baby’s Weight Gain at Ibu Sejati Mandiri Foundation Tuntungan Sub District, Komplek Medan Permai Kota in 2018. Method; This type of research is an analytical survey with a cross sectional approach. The population of this study were all infants aged 0-6 months totaling 32. The sample in this study was a 0-6-month-oldin July to September with a total of 32 babies at Ibu Sejati Mandiri Foundation.Results; There is a long relationship following the baby spa with weight gain infants aged 0-6 months with the results of the calculation p value = 0,000 <α = 0.05. Conclusion;There is Relationship of the length in attending Baby Spa with Weight gain for 0-6-month-olds at Ibu Sejati Mandiri Foundation Medan in 2018. It is suggested for future researchers to be able to make this research as an experience and knowledge, especially about Baby Spa.